Low Elevation and Physical Inactivity are Associated with a Higher Prevalence of Metabolic Syndrome in Ecuadorian Adults: A National Cross-Sectional Study - Juna CF (Dove Medical Press, 2020)
Christian F Juna,1 Yoon Hee Cho,2 Hyojee Joung1,3 1Department of Public Health, Graduate School of Public Health, Seoul National University, Seoul, Republic of Korea; 2Department of Biomedical and Pharmaceutical Sciences, The University of Montana, Missoula, MT, USA; 3Institute of Health and Environment, Seoul National University, Seoul, Republic of KoreaCorrespondence: Yoon Hee ChoDepartment of Biomedical and Pharmaceutical Sciences, The University of Montana, Missoula, MT 59812, USATel +1-406-243-4529Email yoonhee.cho@umontana.eduHyojee JoungGraduate School of Public Health, Seoul National University, Seoul, KoreaTel +82-2-880-2831Email hjjoung@snu.ac.krBackground: Elevation and health-related lifestyles have been associated with the development of metabolic syndrome (MetS). However, such associations have not been investigated extensively in a global context. The present study aimed to determine the associations among elevation of residence, health-related lifestyles, and the risk of MetS in an Ecuadorian adult population.Subjects and Methods: This cross-sectional study was conducted utilizing secondary data from the 2012 Ecuador National Health and Nutrition Survey (ENSANUT-ECU). A total of 6024 adults (1964 men and 4060 women) 20 to 60 years old were included in the study. Elevation was obtained by georeferencing techniques and categorized into low (0– 2000 masl) and high (> 2001 masl). Dietary intake was measured using a 24-hour recall and health-related lifestyle via risk and physical activity standardized questionnaire. MetS was defined on the basis of the National Cholesterol Education Program Adult Treatment Panel III and the Latin American Diabetes Association criteria. Multiple logistic regression analyses were used to examine whether elevation of residence and health-related lifestyles can increase the risk of MetS.Results: Residing at low elevation increased prevalence of MetS in men (1.37; 95% CI, 1.05– 1.76) and elevated fasting glucose in both men (1.80; 95% CI, 1.32– 2.46) and women (1.55; 95% CI, 1.24– 1.93) after adjusting for confounders. Additionally, a lack of physical activity was identified as an important factor that raises the risk of increased waist circumference in both men (2.05; 95% CI, 1.22– 3.45) and women (1.38; 95% CI, 1.05– 1.83) living at low elevation.Conclusion: Our findings suggest that low elevation of residence and physical inactivity are associated with a higher prevalence of MetS in Ecuadorian adults.Keywords: metabolic syndrome, elevation, ENSANUT-ECU, physical activity